2000
DOI: 10.1109/3.823463
|View full text |Cite
|
Sign up to set email alerts
|

Entraining power-dropout events in an external-cavity semiconductor laser using weak modulation of the injection current

Abstract: Abstract-We measure experimentally the effects of injection current modulation on the statistical distribution of time intervals between power-dropout events occuring in an external-cavity semiconductor laser operating in the low-frequency fluctuation regime. These statistical distributions are sensitive indicators of the presence of pump current modulation. Under most circumstances, we find that weak low-frequency (in the vicinity of 19 MHz) modulation of the current causes the dropouts to occur preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 62 publications
2
35
0
Order By: Relevance
“…Counterintuitively, this is possible even by nonresonant perturbations [21]. The more straightforward approach is by resonant parametric perturbations [22,23,24,25,26,27,28] which in the simplest case is a weak sinusoidal signal, but can be any periodic signal. Which orbits can be stabilized by which signals in general can be investigated only if an explicit model of the system is given.…”
Section: Passivation Effects: the Aging Conceptmentioning
confidence: 99%
“…Counterintuitively, this is possible even by nonresonant perturbations [21]. The more straightforward approach is by resonant parametric perturbations [22,23,24,25,26,27,28] which in the simplest case is a weak sinusoidal signal, but can be any periodic signal. Which orbits can be stabilized by which signals in general can be investigated only if an explicit model of the system is given.…”
Section: Passivation Effects: the Aging Conceptmentioning
confidence: 99%
“…While the LK model has been shown to adequately reproduce the main statistical features of the LFF dynamics, such as the IDI distribution with and without modulation [19,29,30], it has also been shown that the LFFs are noise sustained in the LK model [23,24] (i.e., the LFFs are a transient dynamics that dies out when the trajectory finds a stable cavity mode, in deterministic simulations of the LK model). Therefore, it is remarkable that, in spite of the fact that the inclusion of noise is required for simulating sustained LFFs, the model adequately reproduces the symbolic dynamics, and in particular, the correlations present in the sequence of dropouts, and how they vary with the modulation amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…In the LFF regime, the laser output intensity displays irregular, apparently random and sudden, dropouts. In particular, the LFF dynamics has been studied in detail when the laser current is periodically modulated [26,27], not only because the LFFs can be controlled via current modulation [28], but also, from a complex systems perspective, because the interplay of nonlinearity, noise, periodic forcing and delayed feedback leads to entrainment and synchronization [29,30], providing a controllable experimental setup for studying these phenomena. In addition, because the LFF dynamics is excitable, the influence of external forcing has also attracted attention from the point of view of improving our understanding of how excitable systems respond to external signals to encode information [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that introducing strong optical feedback into a frequency-modulated (direct or intracavity EOM) diode laser can enhance the modulation bandwidth [11]- [14], induce modal instabilities [14]- [17], produce mode-locked output pulses [18]- [23], frequency-locked states [24], low-frequency fluctuations [25], [26], and quasi-periodic [24] and chaotic output power [27], depending on the system operating parameters. No single study has considered the full range of parameters over which all of these states are observed.…”
mentioning
confidence: 99%